Small covers over wedges of polygons - Choi, Suyoung; Park, Hanchul (Journal of the Mathematical Society of Japan, 2019)
A small cover is a closed smooth manifold of dimension n having a locally standard Zn 2 -action whose orbit space is isomorphic to a simple polytope. In the paper, we classify small covers and real toric manifolds whose orbit space is isomorphic to the dual of the simplicial complex obtainable by a sequence of wedgings from a polygon, using a systematic combinatorial method of puzzles finding toric spaces.
Keywords: Puzzle; Real toric manifold; Real toric variety; Simplicial wedge; Small cover